Effect of Xylitol Lozenge on Remineralization of Artificial Carious Lesions - In Situ - Sabri İlhan Ramoğlu; Sıddık Malkoç; Zafer Sarı; Abdulkadir Şengün (Galenos Yayinevi, 2009)
The purpose of this study was to evaluate the effect of lozenges containing xylitol on in situ remineralization of artificial carious lesions. Eleven patients (aged between 12 and 15 years old) treated by fixed orthodontic therapy with bilateral maxillary first premolar extractions were included into this study. Each subject wore a modified transpalatal arch that was prepared by adding an acrylic resin to the U region for positioning of the enamel blocks (4X4X3 mm) on it. Three enamel blocks were prepared from the extracted tooth of each patient for both control and experimental groups. Artificial caries lesions were prepared by a low pH solution. This was a two stages study of 14 day periods: no-lozenge and xylitol lozenge (5 times/day, after meals). After each stage, the surface enamel microhardness testing was performed using a Vickers Hardness Tester. Three penetrations were made with a load of 300 g for 15 seconds into the enamel. Friedman's test was used for statistical analyses. The microhardness values were 197.5±127.3, 185.2±106.7, 193.2± 103.4 kgf/mm2 for control, no-lozenge and xylitol groups, respectively. Microhardness results demonstrated that there were no statistically significant differences between amount of remineralization in the control and experimental groups. The results showed that xylitol lozenge was not effective on in situ remineralization of artificial carious lesions but at least non-cariogenic.